Stability of elite freestyle performance from childhood to adulthood - Costa, M. J.; Marinho, D. A.; Bragada, J. A.; Silva, A. J.; Barbosaages, T. M. (Journal of Sports Sciences, 2011)
Stability of athletic performance is important for practitioners and coaches, since it allows the selection of appropriate training methods and prediction of ages for best results. We performed a longitudinal study of 1694 season-best performances of 242 elite-standard swimmers throughout their careers, from 12 to 18 years of age. Mean stability (descriptive statistics and one-way repeated-measures ANOVA, followed by a Bonferroni post-hoc test) and normative stability (Cohen's kappa tracking index and the Pearson correlation coefficient) were determined for seven consecutive seasons. Performance improvements in all events were observed (14.36-18.97%). Bonferroni post-hoc tests verified changes in almost all events assessed. Cohen's kappa demonstrated low stability (0.17-0.27) in relative performance. Pearson correlations only became high from 15 to 16 years in the 50-m and 100-m events, and from 16 to 17 years in the 200-m, 400-m, and 1500-m events. Our results show that: (a) swimmers should display a substantial improvement (14-19%) to become elite standard as adults, such as at 18 years; (b) 16 is the age at which the ability to predict adult performance increases markedly.